Spray Washing Disinfection with Peracetic Acid in the Processing of Fresh-Cut Strawberries: An Alternative for Dipping Techniques - Méndez Galarraga, María Paula (2018)
The effect of spray washing disinfection with peracetic acid (PAA) on quality attributes of fresh-cut strawberries was studied. The effectiveness on native microflora and experimentally inoculated Escherichia coli was also investigated. The responses were evaluated at 0 day and after 7 days of storage (2 °C). PAAconcentration (1?240 mg L−1) and spraying time (11?138 seconds)did not affect the retentions of quality attributes.Optimizing the process at days 0 and 7 allowed to obtain significant reductions for total mesophilic microorganism, molds, and yeasts; furthermore, E. coli reduction was 3.4 log (day 0). All these results suggest that spraying with PAA could be a good disinfection method.